487 Understanding the Medicines Labelling System in a Tertiary Hospital in Kuwait Using Work Domain Analysis. (13th April 2023) - Alhasan, H; Lim, R
Abstract: Introduction: A report by the World Health Organisation highlighted a lack of clarity in medicine labelling regulations in Kuwait and the subsequent risk of patient harm from labelling errors (1). In response, the Undersecretary of the Kuwait Ministry of Health (MOH) issued a ministerial decree governing the labelling of medicines (M.D 4451/2021, June 2021) (2), stipulating a requirement to affix an identification label containing specific patient, medicine, and supplier information on medication packaging. Aim: To develop a map of the Medicines Labelling System (MLS) in a tertiary hospital in Kuwait (TH). Methods: A Work Domain Analysis (WDA) was conducted using qualitative data from 1) semi-structured interviews with a purposive sample of 10 nurses, 10 patients/caregivers, and 10 pharmacists involved in the delivery or administration of medicines to TH patients, as well as 2) an analysis of medicine labelling documents published by the Kuwaiti MOH and TH. After gaining informed consent, one-to-one semi-structured interviews were conducted in TH, in accordance with the latest COVID-19 prevention procedures. All interviews were audio-recorded and transcribed verbatim. Both deductive – informed by Abstraction Hierarchy (AH), the modelling tool of WDA – and inductive thematic analysis was conducted. Results: Thirty participants took part in semi-structured interviews averaging 34 minutes, from which five levels of abstraction in the AH were constructed. The first level, "functional purposes", describes the reason why any given system exists: for the MLS in TH, they were "compliance with regulations, policies, and protocols of the Kuwaiti MOH and TH" and "providing an identification of medicine issued by ISH pharmacies". Five aspects of the second level, "values and priority measures", were identified, including "optimisation of service workflow" and "time-efficient clinical practices." The third level, "purpose-related functions", describes the key functions that need to be in place for the MLS to work; these were "the production of medicines labels", "coordination", and "management of medicines and resources". The last two levels in the AH, "object-related functions" and "physical objects", describe the resources that are required in the MLS, their functionality, and their limitations: there were 16 groups of physical objects, which afforded 19 different functions. Means-ends links showed the crucial relationships and significance between functions at different levels of the AH, the most prominent of which were coordination and communication. Conclusion: TH's MLS is a complex system that was visually represented using an AH, showing the constraints and structure of the work system. The AH constructed a knowledge base. Subsequent analyses of the current system issues may draw on this knowledge, such as a potential analysis of how specific tasks, like the use of labels by nurses within wards, are performed. The limitations of this study included only exploring 'work as imagined' ( i.e., accounts from healthcare staff and documents), which does not fully capture how the MLS functions on a day-to-day basis. Future work will focus on deepening our understanding of the MLS through observations of work in practice. References: 1. World Health Organization. Pharmaceutical Sector Country Profile Questionnaire [Internet]. Geneva (SW): World Health Organisation; 2012 [cited 2022 Aug 20]. Available: https://www.who.int/medicines/areas/coordination/Kuwait_country_profile-questionnaire2012-05-27edited.pdf 2. Undersecretary Office of the Kuwait Ministry of Health, Ministerial Decree for the Labelling of Medicines (M.D 4451/2021). Kuwait City (KW): Kuwait Ministry of Health; 2021.